Effect of potassium sources and rates on arabica coffee yield, nutrition, and macronutrient export - Mancuso, Mauricio Antonio Cuzato [UNESP]; Soratto, Rogério Peres [UNESP]; Crusciol, Carlos Alexandre Costa [UNESP]; Castro, Gustavo Spadotti Amaral (Sociedade Brasileira de Ciência do Solo, 2014)
The use of potassium (K) rock powder can be an alternative for K supply of crops. Thus, to reduce K fertilizer imports from abroad, possibilities of extracting this nutrient from Brazilian rocks are being studied. The objective was to evaluate the effect of phonolite rock powder (F2) as K source (Ekosil®) on the air-dried fruit yield, nutrition and macronutrient export of Arabica coffee. The experiment was carried out on a dystroferric Red Latosol (Typic Haplorthox), in Piraju, São Paulo State, Brazil, in the 2008/09 and 2009/10 growing seasons. The experimental design was a randomized complete block, in a factorial 2 × 3 + 1 arrangement, with four replications. The treatments consisted of two K sources (KCl - 58 % of K2O and F2 - 8.42 % K2O) and three rates ½-, 1-, and 2-fold the K2O rate recommended for coffee, i.e., 75, 150, and 300 kg ha-1 of K2O), plus a control (without K application). Potassium supply increased coffee yield, regardless of the source. Application of source F2 increased coffee yield similarly to KCl at the recommended K rate for coffee (150 kg ha-1 K2O), proving efficient as K supply for coffee. Potassium application increased macronutrient export in coffee, especially in the growing season with higher yield.

A utilização de rochas potássicas moídas ou pó de rocha pode ser uma alternativa para o fornecimento de potássio (K) às culturas. Assim, visando reduzir a importação de fertilizantes potássicos, buscam-se opções para obtenção desse nutriente em rochas brasileiras. Objetivou-se com este trabalho avaliar o efeito, como fonte de K, de uma rocha fonolito moída (F2), comercialmente denominada Ekosil®, na produtividade de grãos em coco, nutrição e exportação de macronutrientes pela cultura do café arábica. Desenvolveu-se o experimento em um Latossolo Vermelho distroférrico, no município de Piraju, SP, nos anos agrícolas de 2008/09 e 2009/10. O delineamento experimental utilizado foi em blocos ao acaso, em esquema fatorial 2 × 3 + 1, com quatro repetições. Os tratamentos foram compostos por duas fontes de K (KCl - 58 % de K2O e F2 - 8,42 % de K2O), três doses (½, 1 e 2 vezes a dose de K2O recomendada para a cultura do café, ou seja, 75, 150 e 300 kg ha-1 de K2O) e uma testemunha (sem aplicação de K). A aplicação de K aumentou a produtividade da cultura do café, independentemente da fonte utilizada. O uso da fonte F2 elevou a produtividade de café em coco, com incrementos semelhantes aos proporcionados pelo KCl na dose de K recomendada para a cultura (150 kg ha-1 de K2O). A aplicação de K aumentou a exportação de macronutrientes pela cultura do café, especialmente em ano de maior produtividade.
Produtividade, nutrição e exportação de macronutrientes pela cultura do café arábica em razão de fontes e doses de potássio
Keywords: Coffea arabica; adubação potássica; pó de rocha; eficiência agronômica; Coffea arabica; potassium fertilization; rock powder; agronomic efficiency